2010
DOI: 10.1039/c004025h
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond spectroscopy on the photochemistry of ortho-nitrotoluene

Abstract: The photo tautomerisations of ortho-nitrotoluene (oNT) and its methylated derivative ortho-ethylnitrobenzene (oENB) have been studied by means of femtosecond spectroscopy and (TD)-DFT computations. In UV/Vis transient absorption spectroscopy a band peaking at 400 nm is seen to rise in a bi-modal manner with time constants of 1-10 ps and 1500 ps. Femtosecond stimulated Raman experiments clearly identify aci-nitro forms as the spectroscopic carriers of the 400 nm band. The assignment of the Raman spectra is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 55 publications
6
73
0
Order By: Relevance
“…All suggested uncaging mechanisms for oNB cages require ESIPT as a first step, [9,10] which has recently been studied employing femtosecond spectroscopy. [11] The overall quantum yield of uncaging is commonly seen as being limited by a competition between the reaction from S 1 or T 1 and the radiationless decay from these states. However, our computations suggest a different picture for the decay from the S 1 state.…”
Section: CMmentioning
confidence: 99%
“…All suggested uncaging mechanisms for oNB cages require ESIPT as a first step, [9,10] which has recently been studied employing femtosecond spectroscopy. [11] The overall quantum yield of uncaging is commonly seen as being limited by a competition between the reaction from S 1 or T 1 and the radiationless decay from these states. However, our computations suggest a different picture for the decay from the S 1 state.…”
Section: CMmentioning
confidence: 99%
“…In spite of the fact that this is a rather simplistic model for RR spectra, we have demonstrated in previous work that it usually results in satisfactory agreement with experimental spectra for a variety of different molecules. [30,[32][33][34][35] With these approximations, the scattering tensor a 1l  à fi , which determines the resonance Raman intensities, takes the following form as shown in Equation (1): [36][37][38][39] …”
Section: Theoretical Background Of Rr Calculationsmentioning
confidence: 99%
“…17 ln the growing family of PPGs, the o-nitrobenzyl group is one of the oldest, but still widely used groups, mainly due to its robustness and relative photophysical insensitivity to interfering influences. There have been many studies, both experimental and computational, on the mechanism of the photoinduced decomposition of this kind of PPGs [18][19][20][21][22][23][24][25][26] but many unanswered questions remain, such as the impact of substituents in various positions, and the origin of an intriguing kinetic isotope effect. 27,28 For example, it has been shown that the quantum yields ϕ for the disappearance of nitrobenzyl PPGs, or those for the release of the leaving groups, depend strongly on the chemical character of the leaving group (LG).…”
Section: Introductionmentioning
confidence: 99%
“…24,31,32 It would therefore appear reasonable to assume that the height of this barrier scales with the strength of the critical C-H bond (marked red in Scheme 2). We based our computational exploration on the premise that this bond strength, although it is certainly much smaller in the (singlet or triplet) excited state, is affected similarly by the presence of different LGs X as it is in the ground state.…”
mentioning
confidence: 99%